Chronic vein insufficiency (CVI) in patients after stroke - Kwolek, Andrzej; Orzeł, Agnieszka; Czarnecka, Greta; Wojtyna, Agnieszka; Szydełko, Magdalena; Majka, Małgorzata (European Journal of Clinical and Experimental Medicine, 2005)
<h2 class="block-title" style="box-sizing: border-box; font-family: Lato, sans-serif; font-weight: bold; line-height: 1.1; color: #010101; margin-top: 23px; margin-bottom: 11.5px; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; letter-spacing: 0.1px; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Abstract <div class="field-name-field-autorzy-" style="box-sizing: border-box; font-size: 14px; color: #010101; display: inline-block !important; float: left !important; padding: 10px 24px 0px 0px !important; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;"> Chronic vein insufficiency (CVI) is a disturbance of blood outflow throw the superficial and deep veins in lower limbs. The aim of the study is estimation of frequency and the advance in chronic vein insufficiency in patients in Rehabilitation Ward. We estimated also the influence of complex rehabilitation on progress of disease and dependence between occurrence of CVI and sex and other diseases. Material and methods: We examined 244 patients (112 female and 132 male). Patients were divided into two groups: patients after stroke and the other patients treated in rehabilitation ward. Each patient was examined on first and last day of hospitalisation: we estimated risk factors of CVI and we also measured circumference of lower limb 5 cm above medial ankle and widest circumference of calf. We also estimated the degree of advance of CVI using clinical classification of CEAP scale. Results: Based on the study results that frequency of CVI in patients of rehabilitation ward is high, it is estimated on 74,5% and it is a considerably higher than in general population – 42%. CVI occurs more often in patients with stroke, cardiac disorders, hypertension In the study there was found correlation between frequency of CVI and sex. The average level of CVI in patients after stroke is higher (1.88) than the other group of patients (1.21). Due to the complex rehabilitation we obtain reduce of circumference of lower limb and lowering of patients complaints. Conclusions: Early and complex rehabilitation reduces in large range symptoms of CVI. The lack of early and diagnosis prophylaxis and treatment can cause severe complication and lower quality of patients life. It is worth to carry wide education about CVI among doctors and patients.